EDUKASI DAN KONSELING RAGAM METODE KONTRASEPSI DI DESA SIMANINGGIR KECAMATAN ANGKOLA BARAT - Munawarah, Masrina (Universitas Aufa Royhan Di Kota Padangsidipuan, 2021)
Good knowledge about the various contraceptives is an important thing that becomes the basis for women to choose contraception. In addition, counseling can also be used as a good method in helping women to decide on a contraceptive method that suits their needs. This education and counseling activity for various contraceptive methods is carried out as a form of community service in the fostered village of Aufa Riyhan University, namely Simaninggir Village, West Angkola District. A total of 40 women of childbearing age participated in this activity. The evaluation of the activity showed that there was an increase in participants' understanding and ability to choose contraception after this activity was carried out. This education and counseling is expected to be a method of counseling that is carried out regularly and continuously to achieve community welfare through increasing the coverage of contraceptive use.